Glutamine-Induced Secretion of Intestinal Secretory Immunoglobulin A: A Mechanistic Perspective - Ren, Wenkai; Wang, Kai; Yin, Jie; Chen, Shuai; Liu, Gang; Tan, Bie; Wu, Guoyao; Bazer, Fuller W.; Peng, Yuanyi; Yin, Yulong (Frontiers in Immunology, 2016)
Secretory IgA (SIgA) is one important line of defense in intestinal mucosal surface to protect the intestinal epithelium from enteric toxins and pathogenic microorganisms. Multiple factors, such as intestinal microbiota, intestinal cytokines and nutrients, are highly involved in intestinal production of SIgA. Recently, glutamine has been shown to affect intestinal SIgA production, however, the underlying mechanism by which glutamine promotes intestinal SIgA secretion remains to know. Here, we review the current knowledge regarding glutamine in intestinal immunity, and show that glutamine enhances intestinal SIgA production may through intestinal microbiota, intestinal antigen sampling and presentation, induction pathways for SIgA production by plasma cells (both T-dependent and T-independent pathway), and even SIgA transportation. Altogether, the glutamine-intestinal SIgA axis has broad therapeutic implications for intestinal SIgA -associated diseases, such as celiac disease, allergy, and inflammatory bowel disease.